Hubungan Riwayat Keluarga, Aktivitas Fisik, dan Pola Makan terhadap Kejadian Diabetes Melitus - Irayani, Salsa Putri (Journal of Public Health Education, 2024)
Introduction: One of the most common non-communicable diseases is diabetes mellitus. Diabetes Mellitus is a chronic metabolic disease or disorder characterized by high blood sugar levels (hyperglycemia). Objectives: to determine the relationship between family history, physical activity, and eating patterns on the incidence of diabetes mellitus at the Tanah Sareal Health Center, Bogor City, in 2023. Method: The research method used is a quantitative approach with an observational analytic research design using a cross-sectional research design. The population in this study were all patients of the Non-Communicable Diseases Polyclinic in the Tanah Sareal Health Center, Bogor City, totaling 1,922 people with a total sample of 50 respondents. How can samples be taken using accidental sampling and collected using a questionnaire? Data analysis used the chi-square test. Result: The results showed that there was a relationship between family history and a p-value of 0.013 (p<0.05), there was a relationship between physical activity and a p-value of 0.006 (p<0.05), and there was no relationship between diet and a p-value of 1,000 (p>0.005) for the incidence of Diabetes Mellitus at the Tanah Sareal Health Center Conclusion: There is a significant relationship between family history and physical activity with the incidence of Diabetes Mellitus at the Tanah Sareal Health Center in 2023.